Characterization of the functional effects of ferredoxin 1 as a cuproptosis biomarker in cancer - Li, Xiang; Dai, Zihan; Liu, Jincheng; Sun, Zhenqian; Li, Na; Jiao, Guangjun; Cao, Hongxin (Frontiers in Genetics, 2022)
Background: Cuproptosis is a recently discovered form of programmed cell death. Ferredoxin 1 (FDX1) is a key gene that mediates this process. However, the role of FDX1 in human tumors is not clear. Methods: We comprehensively analyzed the differential expression and genetic alterations of FDX1 using multiomics data from The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression (GTEx) database. Subsequently, we explored the association between FDX1 and tumor parameters such as genomic instability, RNA methylation modifications, immune infiltration and pathway activity. In addition, we performed functional enrichment analysis and assessed the sensitivity potential of FDX1-related drugs. Finally, we experimentally verified the functional effects of FDX1. Results: The analysis revealed differential expression of FDX1 in a variety of tumors. By analyzing the association of FDX1 expression with genomic instability, immune cell infiltration, signaling pathway etc. We explored the role of FDX1 in regulating cell activity. Also, we evaluated the function of FDX1 in biologic process and drug sensitivity. Our experimental results demonstrated that FDX1 exerts its antitumor effects through cuproptosis in liver hepatocellular carcinoma and non-small cell lung cancer cell lines. Conclusion: Our study reveals the functional effects of FDX1 in tumors and deepens the understanding of the effects of FDX1. We validated the inhibitory effect of FDX1 in copper induced cell-death, confirming the role of FDX1 as a cuproptosis biomarker.